Energy Production, Load and Battery Management Framework with Supporting Methods for Smart Microgrids (Springer Nature, 2025)
This open access book provides an overview of the results of a large university collaboration addressing the emerging topic of distributed, localized energy grids and also smart grids. The authors discuss promising, consolidated results from their consortium research activities from the past decade. The methods described achieve unprecedented accuracy levels within reasonable run-times, compatible with on-line monitoring and forecasting as needed for smart grids.